Meta-Analysis of Re-perfusion Injury and Ischaemic Conditioning in Limb Surgery - Utomo, Pamudji Utomo; Yudistira, Mochamadsyah Beizar (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Pneumatic tourniquet commonly used for orthopedic surgery is associated with morbidity related to ischemia-reperfusion injury. Ischaemia conditioning (IC) had shown beneficial effects to attenuate these outcomes. This study aimed to systematically review the evidence of IC effect on outcomes of the patient undergoing orthopedic surgery.Subjects and Method: This was a systematic review and Meta-Analysis conducted through the online database search from PubMed, Central, Clinicaltrials.gov, and Scopus with topics related to IC and all possible orthopedic surgical interventions. Articles were searched with Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) protocols used keywords